89Zr-mAb3481 PET for HER3 tumor status assessment during lapatinib treatment. Issue 8 (17th November 2017) - Pool, Martin; Kol, Arjan; de Jong, Steven; de Vries, Elisabeth G. E.; Lub-de Hooge, Marjolijn N.; Terwisscha van Scheltinga, Anton G.T.
ABSTRACT: Treatment of human epidermal growth factor receptor 2 (HER2)-driven breast cancer with tyrosine kinase inhibitor lapatinib can induce a compensatory HER3 increase, which may attenuate antitumor efficacy. Therefore, we explored in vivo HER3 tumor status assessment after lapatinib treatment with zirconium-89 ( 89 Zr)-labeled anti-HER3 antibody mAb3481 positron emission tomography (PET). Lapatinib effects on HER3 cell surface expression and mAb3481 internalization were evaluated in human breast (BT474, SKBR3) and gastric (N87) cancer cell lines using flow cytometry. Next, in vivo effects of daily lapatinib treatment on 89 Zr-mAb3481 BT474 and N87 xenograft tumor uptake were studied. PET-scans (BT474 only) were made after daily lapatinib treatment for 9 days, starting 3 days prior to 89 Zr-mAb3481 administration. Subsequently, ex vivo 89 Zr-mAb3481 organ distribution analysis was performed and HER3 tumor levels were measured with Western blot and immunohistochemistry. In vitro, lapatinib increased membranous HER3 in BT474, SKBR3 and N87 cells, and consequently mAb3481 internalization 1.7-fold (BT474), 1.4-fold (SKBR3) and 1.4-fold (N87). 89 Zr-mAb3481 BT474 tumor uptake was remarkably high at SUVmean 5.6±0.6 (51.8±7.7%ID/g) using a 10 μg 89 Zr-mAb3481 protein dose in vehicle-treated mice. However, compared to vehicle, lapatinib did not affect 89 Zr-mAb3481 ex vivo uptake in BT474 and N87 tumors, while HER3 tumor expression remained unchanged. In conclusion, lapatinib increased in vitro HER3 tumor cell expression, but not when these cells were xenografted. 89 Zr-mAb3481 PET accurately reflected HER3 tumor status. 89 Zr-mAb3481 PET showed high, HER3-specific tumor uptake, and such an approach might sensitively assess HER3 tumor heterogeneity and treatment response in patients.